PENGARUH CUSTOMER EXPERIENCE DAN HEDONIC SHOPPING VALUE TERHADAP IMPULSE BUYING PADA APLIKASI SHOPEE - Refiyahya, Afifah Huda; Yulinda, Ade Tiara (UM. Bengkulu, 2025)
This study aims to determine the effect of Customer Experience and Hedonic Shopping Value on Impulse Buying on the Shopee Application (Case Study of FEB Students Class of 2021, University of Muhammadiyah Bengkulu). This type of research is a type of quantitative descriptive research, the object of this research is FEB Students Class of 2021, Universitas Muhammadiyah Bengkulu. The population in the study were Shopee Application Consumers in the Muhammadiyah Bengkulu University environment with a research focus on 2021 Faculty of Economics and Business Students as the object of research. In determining the number of samples used in this study using the formula n x 10 observed variables (indicators) with 150 respondents. The data collection method uses a questionnaire that uses a Likert scale measuring instrument. Data analysis techniques using Multiple Linear Regression Analysis Tests and Hypothesis Tests. Research results in the t test (partial) that the Customer Experience and Hedonic Shopping Value variables have a positive and significant effect on Impulse Buying. In the f test (Simultaneously) the variables Customer Experience and Hedonic Shopping Value together have a significant influence on Impulse Buying in the Shopee application on FEB Students, Class of 2021, Universitas Muhammadiyah Bengkulu. Keywords: Customer Experience. Hedonic Shopping Value, Impulse Buying